2009
DOI: 10.1007/s10143-009-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival following stereotactic radiosurgery for newly diagnosed and recurrent glioblastoma multiforme: a multicenter experience

Abstract: Despite decades of clinical trials investigating new treatment modalities for glioblastoma multiforme (GBM), there have been no significant treatment advances since the 1980s. Reported median survival times for patients with GBM treated with current modalities generally range from 9 to 19 months. The purpose of the current study is to retrospectively review the ability of CyberKnife (Accuray Incorporated, Sunnyvale, CA, USA) radiosurgery to provide local tumor control of newly diagnosed or recurrent GBM. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 42 publications
0
35
0
1
Order By: Relevance
“…The median post-SRS survival varies between 6.5 months [25] and 26 months [13]. These differences may be due to the inhomogeneity among the studies (clinical features of the patients, histological type, modalities of treatment after SRS, and so forth).…”
Section: Discussionmentioning
confidence: 99%
“…The median post-SRS survival varies between 6.5 months [25] and 26 months [13]. These differences may be due to the inhomogeneity among the studies (clinical features of the patients, histological type, modalities of treatment after SRS, and so forth).…”
Section: Discussionmentioning
confidence: 99%
“…SRT has become widely used for the treatment of nonresectable intracranial masses, either intraaxial or involving the skull base. Experience with skull base meningiomas and gliomas in humans suggests responses may approach those seen with surgically resected tumors 185, 186. One of the major advantages of SRT techniques is the ability to deliver the therapeutic dose of radiation in 2–5 fractions (single dose treatments are referred to as stereotactic radiosurgery [SRS]) compared to 16–20 fractions for standard radiation protocols.…”
Section: Radiation Therapymentioning
confidence: 99%
“…In a recently published multicenter study, SRS with CK treatment was well tolerated although the median survival time did not exceed 7 mo (range, 1-34 mo) in patients with recurrent GBM. 5 While the antiproliferative effects of irradiation on glioma cells have been extensively studied, little is known about the effects of ionizing radiation on migration/invasion of GBM cells and even less is known about potential differences in biological effects between different SRS irradiation modality. It has previously been reported that in vitro cultured GBM cells may increase their migration/invasion ability after irradiation.…”
Section: Introductionmentioning
confidence: 99%